Peningkatan Teknik Dasar Long Service dengan Metode Drill pada Olahraga Bulutangkis PB Warda Kota Padang - Suci Maisarah; Anggun Permata Sari; Ridho Bahtra; Fahmil Haris (SPRINTER: Jurnal Ilmu Olahraga, 2026)
This study aimed to analyze the improvement of basic long service technique through the drill method among badminton athletes at PB Warda, Padang City. A quantitative one-group pretest-posttest experimental design was employed. The population consisted of 20 athletes, while 12 male athletes aged 9–12 years were selected using purposive sampling. The intervention comprised 16 sessions emphasizing repeated practice of ready position, racket swing, shuttlecock contact, body-weight transfer, and target accuracy. The instrument was a 10-attempt long-service accuracy test with a reported validity coefficient of 0.54 and reliability of 0.77. Data were analyzed using descriptive statistics, normality testing, and a paired-samples t test. The mean score increased from 21.67±6.87 to 25.17±5.51, yielding a mean gain of 3.50 points. Reanalysis of the raw scores produced t(11)=4.64, p<0.001, with a large effect size (dz=1.34). The proportion of athletes in the low category decreased from 50.0% to 16.7%. These findings indicate that a structured drill method effectively improves the accuracy and consistency of long-service performance among PB Warda athletes.